Penetapan Suku Bunga pada Bank Perkreditan Rakyat Jawa Timur Cabang Jember Perspektif Hukum Ekonomi Islam - Ervina Maftuhatun Nurul Qomariah; Rumawi Rumawi; Nina Agus Hariarti; Puput Lestari (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
Bank interest or usury is simply interpreted as an expression of remuneration for the use of money lent or the use of funds. Communities who need funds for business will provide remuneration to banks that have provided loans in the form of credit for additional business capital, investment and working capital in trade. The aims of this study are: 1) To find out the determination of interest rates at BPR Jember branches. and 2). Knowing the perspective of Islamic economic law on the determination of interest rates at the East Java BPR Jember branch. Research method The type of research used by researchers is empirical research, namely where the empirical legal research method originates from facts quoted directly from the words and behavior levels of research informants, by conducting interviews while conducting direct observation of research locations. This empirical research is used to directly identify the informants and retrieve data from the results of their research directly and in the form of direct documentation as data to strengthen the results of the research. The purpose of this research is to study in depth about the determination of interest rates at the Madani Blooms National Capital Bank in Panti Jember District. Then from the results of this study, there are conclusions from researchers regarding the determination of interest rates in BPR Jember.